A Descriptive Study of Some of the Dento-Gingival Components of Esthetics of Patients at a Tertiary Care-center in the Eastern Part of Nepal - Arati Sharma (International Journal of Dentistry)
Background. The purpose of this study was to observe and describe some of the dento-gingival components of esthetics like the mean gingival zenith position (GZP) with respect to the vertical bisected midline axis (VBM), relative gingival zenith level (GZL) of lateral incisors (LIs), heights and widths of central incisors (CIs), LIs, and their ratios. Materials and Methods. This cross-sectional, hospital-based, descriptive study was conducted from Feb 2019 to Aug 2019. Ethical clearance was taken from the Institutional Review Committee of B. P. Koirala Institute of Health Sciences. Convenience sampling was done. Variables (above mentioned) were marked and measured on the casts with a calibrated digital vernier caliper and entered in the data sheet, and descriptive analysis was done with SPSS version 20. Results. A total of 210 subjects of the age group 18–25 years were included in the study. Mean GZP of the right CI was 0.49 ± 0.54 mm, of the left CI was 0.42 ± 0.43 mm, of the right LI was 0.20 ± 0.34 mm, of the left LI was 0.04 ± 0.35 mm, of the right C (Canine) was 0.023 ± 0.38 mm, and of left C was 0.07 ± 0.38 mm. Mean relative GZL of LI was about 0.40–0.41 mm below the reference line. Mean height of the right CI was 9.34 ± 0.93 mm, and that of the left CI was 9.31 ± 0.87 mm; that of the right LI was 7.91 ± 0.98 mm, and that of the left LI was 7.92 ± 0.91 mm. Mean width of the right CI was 8.34 ± 0.57 mm, and that of the left CI was 8.38 ± 0.48 mm; that of the right LI was 6.62 ± 0.58 mm, and that of the left LI was 6.66 ± 0.53 mm. Conclusions. Mean GZP of each upper anterior tooth was distally located with respect to VBM; that of CI was more distally placed than LI and C. Relative GZL of LI was below the reference line. The central incisor width/height ratio obtained was >80% that means a squarer tooth.